Preparation and Characterization of Cacao Waste As Cacao Vinegar And Charcoal - Mohammad Wijaya; Muhammad Wiharto (UNEJ e-Proceeding, 2016)
Potential waste are still abundant cocoa that has not been widely used by most people, especially farmers who are in the cacao plantations. One way to reduce the building of waste biomass pyrolysis technology which produces smoke that can be inserted into the fluid (liquid smoke and other organic materials) charcoal and some gas (hydrocarbon and methane, H2, and CO2). The purpose of this research is to produce cacao vinegar, activ carbon and charcoal. The results of this research that the pod husks produce ethanol of benzene of 1: 2 at 12.89%, content of hemicellulose 19,97%, cellulose 21,80% and lignin 47.96%. GC MS analysis for cacao waste  Majene produce n -Buthane 8.72%, acetic acid 64.11%, 3.67% cyclopentane, 2 (3H) furanone 2.74%, 1.59% 2 furan methanol, and Mequinol 3.40%. FT-IR analysis for cacao waste  Majene district showed that the wave number 1153.43 cm-1 indicated to dehydration and depolymerization of cellulose and hemicellulose content. Changes aromatic peak at 1737.86 cm -1 indicates the presence of C-H, lignin. While the wave number 3448.72 cm-1 indicate the presence of hydroxyl group (O-H) and the absorbance of 717.52 to 617.22 cm-1 indicates the presence of C = C-H (Aromatic H). XRD analysis results will be obtained the degree of crystallinity charcoal pod husks of 26.60% Waste cocoa with pyrolysis technologies to reduce carbon emissions on the environment in order to be sustainable development and environmental conservation in order to maintain and sustainably.